Design and Development of an Android-Based Application for Hydroponic Introduction and Learning Media - Fitriyah, Nur Qodariyah; Rosyidah, Ulya Anisatur; Oktavianto, Hardian (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2025)
Learning media will make it easier for people to learn hydroponic vegetable planting material compared to books because there are visualizations of images and videos so that it will be understood more quickly than just reading. Android is one of the open-source programming languages that allows makers to modify and distribute the results of making applications freely and freely. Developing learning media for hydroponic vegetable planting using Android will make it easier for readers because this application can be used anywhere without carrying more weight than books. In this learning media to be built, the advantages of this application are the visualization of attractive graphics, and simple decision support features related to the implementation of hydroponic farming, which includes capital and available land, as well as suitable plant species. The application has been successfully made, and based on the test results, it can be concluded that it can be appropriately used and produce results according to the design. The suggestions from this research are related to the application's appearance, which can still be developed to be more attractive.